Psoas muscle area is not representative of total skeletal muscle area in the assessment of sarcopenia in ovarian cancer. Issue 4 (16th May 2017) - Rutten, Iris J.G.; Ubachs, Jorne; Kruitwagen, Roy F.P.M.; Beets‐Tan, Regina G.H.; Olde Damink, Steven W.M.; Van Gorp, Toon
Abstract: Background: Computed tomography measurements of total skeletal muscle area can detect changes and predict overall survival (OS) in patients with advanced ovarian cancer. This study investigates whether assessment of psoas muscle area reflects total muscle area and can be used to assess sarcopenia in ovarian cancer patients. Methods: Ovarian cancer patients ( n = 150) treated with induction chemotherapy and interval debulking were enrolled retrospectively in this longitudinal study. Muscle was measured cross sectionally with computed tomography in three ways: (i) software quantification of total skeletal muscle area (SMA); (ii) software quantification of psoas muscle area (PA); and (iii) manual measurement of length and width of the psoas muscle to derive the psoas surface area (PLW). Pearson correlation between the different methods was studied. Patients were divided into two groups based on the extent of change in muscle area, and agreement was measured with kappa coefficients. Cox‐regression was used to test predictors for OS. Results: Correlation between SMA and both psoas muscle area measurements was poor ( r = 0.52 and 0.39 for PA and PLW, respectively). After categorizing patients into muscle loss or gain, kappa agreement was also poor for all comparisons (all κ < 0.40). In regression analysis, SMA loss was predictive of poor OS (hazard ratio 1.698 (95%CI 1.038–2.778), P = 0.035). No relationship with OS was seen for PA or PLW loss. Conclusions: Change in psoas muscle area is not representative of total muscle area change and should not be used to substitute total skeletal muscle to predict survival in patients with ovarian cancer.